The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.mce.2009.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Expression and subcellular localization of CRH and its receptors in human endometrial cancer

Abstract: CRH and its receptors are expressed in human normal endometrial cells, where they are associated to anti-proliferative progesterone-like activity. We aimed to investigate CRH, CRH-R1 and CRH-R2 expression and intracellular localization in human endometrial cancers and their relationships with tumor biological parameters. Surgical specimens were obtained from 51 untreated endometrial cancer patients and immunohistochemistry for CRH, CRH receptors, ER, PR and Ki-67 was performed. We found a diffuse cytoplasmic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
(44 reference statements)
0
14
0
4
Order By: Relevance
“…The surrounding normal endometrial glands showed a typical paranuclear/apical pattern for CRF and stained for CRF2 receptor at the nuclear level, whereas CRF1 receptor staining was similar to that observed in tumors. CRF2 cytoplasmic pattern was associated with more advanced FIGO stage disease [34,35]. In contrast, positive correlation was found between CRF1 and progesterone receptor expression suggesting a potential role of this receptor in the characterization of less aggressive tumors.…”
Section: Crf and Endometrial Carcinomamentioning
confidence: 82%
“…The surrounding normal endometrial glands showed a typical paranuclear/apical pattern for CRF and stained for CRF2 receptor at the nuclear level, whereas CRF1 receptor staining was similar to that observed in tumors. CRF2 cytoplasmic pattern was associated with more advanced FIGO stage disease [34,35]. In contrast, positive correlation was found between CRF1 and progesterone receptor expression suggesting a potential role of this receptor in the characterization of less aggressive tumors.…”
Section: Crf and Endometrial Carcinomamentioning
confidence: 82%
“…Corticotropin-releasing factor (CRF) and Urocortin (Ucn) have been found to be over-expressed in human reproductive tumors such as ovarian cancer (Suda et al 1986), endometrial adenocarcinoma (Miceli et al 2009), and hydatidiform mole (Okamoto et al 1990). However, the special effects of CRF family peptides on cellular apoptosis in reproductive tumors are controversial at present.…”
Section: Introductionmentioning
confidence: 99%
“…Antigen-antibody complexes were visualized with 3,3′-diaminobenzidine (DAB) solution (1-mM DAB, 50-mM Tris–HCl buffer [pH 7.6], and 0.006% H 2 O 2 ) and counterstained with hematoxylin. Human placental tissue was used as a positive control for CRH, CRHR1, and CRHR2 immunostaining 14. As a negative control, normal goat or mouse immunoglobulin G was used instead of the primary antibody.…”
Section: Methodsmentioning
confidence: 99%
“…Of note, the expression of CRH and its receptors has also been reported in several types of carcinoma 12,13. Specifically, Miceli14 reported CRH, CRHR1, and CRHR2 immunoreactivity in endometrial carcinoma. Although stress is known to be a promoter of tumor growth,15 it remains unclear whether CRH, CRHR1, or CRHR2 immunoreactivity in endometrial carcinoma is a risk factor for poor prognosis.…”
mentioning
confidence: 92%